1993
DOI: 10.1017/s0960258500001549
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear proteins and the onset of cell proliferation in root meristems ofPisum sativum: QP47 a novel acidic protein

Abstract: A protein named QP47 has been purified from quiescent nuclei of root meristems of Pisum sativum, and used to prepare a polyclonal antibody. Immunolocalization of this protein with fluorescent probes revealed a nuclear distribution of thread-like structures. However, the relationship between the distribution of QP47 immunofluorescence and the structural organization of the chromatin required further investigation. The decrease in content of this protein in the nuclei of embryo cells seems to be correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…In fact, the 47 kDa protein was recognized (data not 295 shown) by the QP47 polyclonal antibody prepared previously (Chiatante and Onelli, 1993). In fact, the 47 kDa protein was recognized (data not 295 shown) by the QP47 polyclonal antibody prepared previously (Chiatante and Onelli, 1993).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In fact, the 47 kDa protein was recognized (data not 295 shown) by the QP47 polyclonal antibody prepared previously (Chiatante and Onelli, 1993). In fact, the 47 kDa protein was recognized (data not 295 shown) by the QP47 polyclonal antibody prepared previously (Chiatante and Onelli, 1993).…”
Section: Resultsmentioning
confidence: 89%
“…We had shown previously that a considerable amount of QP47 was present in nuclei of meristematic root cells after 6 h of imbibition (Chiatante and Onelli, 1993). In the same paper, the comparison of the QP47 content at different times of germination demonstrated that the amount of this nuclear protein must decrease to an undetectable level before cell proliferation can be resumed.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations